2009
DOI: 10.1007/s12602-008-9000-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of an Antilisterial Bacteriocin Produced by Lactobacillus sakei CWBI-B1365 Isolated from Raw Poultry Meat and Determination of Factors Controlling its Production

Abstract: Amongst 101 lactic acid bacteria isolated from meat and fish samples, strain CWBI-B1365, identified as Lactobacillus sakei, was found to produce the subclass IIa bacteriocin sakacin G. Partial sequencing of the gene involved in the biosynthetic pathways revealed an unusual gene organisation in that the accessory gene associated with bacteriocin transport did not occur immediately downstream of the gene encoding an ABC transporter, but upstream of the putative immunity gene and encoded on the opposite DNA stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
2
10
1
Order By: Relevance
“…Activity Spectrum of Cell-Free Supernatant Antimicrobial activity was estimated by agar diffusion assay [10]. Listeria strains were grown in BH liquid medium for 24 h at 37°C.…”
Section: Strains Media and General Genetic Techniquesmentioning
confidence: 99%
“…Activity Spectrum of Cell-Free Supernatant Antimicrobial activity was estimated by agar diffusion assay [10]. Listeria strains were grown in BH liquid medium for 24 h at 37°C.…”
Section: Strains Media and General Genetic Techniquesmentioning
confidence: 99%
“…Consequently, the preserving capacity of naturally occurring bacteria in food is now of the greatest interest (Lind and others 2005). Lactic acid bacteria (LAB) have been widely researched for their antimicrobial properties through the production of organic acids, hydrogen peroxide, and bacteriocins (Corsetti and others 1998; Okkers and others 1999; Cleveland and others 2001; Dortu and others 2009). However, new studies have related the production of antifungal compounds by these bacteria (De Muynck and others 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This revealed that final pH is independent of starting pH and coincides with the results by Dortu et al . () reporting that the other LAB – Lactobacillus sakei at the end of cultivation in initial pH 5, 5.5, 6 and 6.5 dropped the medium pH to a value 4.1 ± 0.1.…”
Section: Resultsmentioning
confidence: 98%
“…These data are similar to results obtained by Dortu et al . () for L. sakei sakacin G production during nonregulated and regulated pH cultures when initial pH 6 and pH 6.5 of noncontrolled pH cultures were optimal for antilisterial activity.…”
Section: Resultsmentioning
confidence: 99%